Alternative flow cytometry strategies to analyze stem cells and cell death in planarians. Issue 2 (16th March 2016) - Peiris, Tanuja Harshani; García‐Ojeda, Marcos E.; Oviedo, Néstor J.
Abstract: Planarians possess remarkable stem cell populations that continuously support cellular turnover and are instrumental in the regeneration of tissues upon injury. Cellular turnover and tissue regeneration in planarians rely on the proper integration of local and systemic signals that regulate cell proliferation and cell death. Thus, understanding the signals controlling cellular proliferation and cell death in planarians could provide valuable insights for maintenance of adult body homeostasis and the biology of regeneration. Flow cytometry techniques have been utilized widely to identify, isolate, and characterize planarian stem cell populations. We developed alternative flow cytometry strategies that reduce the number of reagents and the time of sample preparation to analyze stem cells and cell death in planarians. The sensitivity of these methods is validated with functional studies using RNA interference and treatment with γ irradiation or stressful conditions that are known to trigger cell death. Altogether, we provide a community resource intended to minimize adverse effects during ex vivo studies of stem cells and cell death in planarians.